PENERAPAN SAK ETAP DENGAN BENAR PADA SISTEM KEUANGAN PT DAMAI GADAI - Grace Monika Indah Prastiwi; Tri Ratna Pamikatsih (Jurnal Ilmiah Akuntansi, 2025)
Financial reports are a communication tool for a company or parties that need the financial report. The parties that need it are usually called internal parties and external parties. In this case, the financial report has financial accounting standards. The financial standardization of entities without public accountability (SAK ETAP) is a financial standard used by companies that are entities without public accountability such as PT Damai Gadai. The purpose of this study is to determine the application of SAK ETAP to the financial statements of PT Damai Gadai. This study uses a descriptive method, to determine the application of PT Damai Gadai's financial statements in accordance with SAK ETAP. Descriptive method, to determine the comparison of PT Damai Gadai's financial statements with reports based on SAK ETAP. The steps taken to obtain PT Damai Gadai's financial report data by conducting observations of data collection, then conducting analysis, and conducting interviews. The results of this study indicate that PT Damai Gadai's financial statements have not implemented financial statements according to SAK ETAP standards. This is due to the limited knowledge they have.